Legal Protection Of Traditional Rights Togutil Tribal Community In Halmahera Forest Inside - Hi. Soleman, Saiful; Kokodaka, Sudiar (CV. Inara, 2022)
The protection of the rights of the Customary Law Community (MHA) at the conceptual level has been guaranteed by the constitution. The existence of articles 18 B paragraphs (2) and 28I (3) of the 1945 Constitution as well as sectoral laws (Law Number 5 of 1960 concerning Agrarian Principles. empirical normative research, the Togutil tribal people still live nomadic in the forest and there are who have settled in a settlement around the forest, that the traditional rights of the indigenous peoples of the Togutil tribe are defined as a group of people who have something in common, to live in a certain area, either because of blood relations or kinship (geneological), clans and clans, and/or regional (geological) relations, have various customary law regulations.